Catalase-negative, methicillin-resistant Staphylococcus aureus as a cause of septicemia - Ana Lúcia Innaco de Carvalho; Rosemeire Cobo Zanella; Luciane Parra Yoshikawa; Sérgio Bokermann; Maria Luiza L.S. Guerra; Jane Harumi Atobe; Marguerite Lovgren (Sociedade Brasileira de Patologia Clínica, 2003)
A catalase-negative methicillin-resistant Staphylococcus aureus (MRSA) was isolated from blood, venous catheter spike and bone marrow collected from an HIV-positive man with lobar pneumonia and sepsis after ten days of hospitalization. The isolate was resistant to oxacillin (positive for penicillin-binding protein 2'), ceftriaxone, clindamycin and clarithromycin, and susceptible to vancomycin. This is the first case of septicemia due to a catalase-negative S. aureus reported in Brazil, and, to our knowledge, it is the first case of catalase-negative MRSA reported in the literature. We believe that the patient acquired the S. aureus infection within the hospital environment since it was isolated ten days after hospitalization, it was isolated in a venous catheter spike, and the antibiotic resistance profile is similar to other S. aureus isolates recovered from infections in our hospital.